Chitosan/metal oxide nanocomposites: synthesis, characterization, and antibacterial activity - Mizwari, Zirar M.; Oladipo, Akeem Adeyemi; Yilmaz, Elvan (Taylor & Francis As, 2021)
With the growing concern of biofilm-associated infections and drug-resistant bacteria, an increasing interest in developing novel antibacterial agents is an urgent priority. Metal oxide-based polymeric materials are able to distinguish mammalian cells from bacterial cells and thus provide long-term antibacterial growth inhibition. Herein, we report the preparation of MgO, NiO and chitosan-coated metal oxide (CS-MO) nanocomposites via a simple in situ chemistry approach. Fourier transform infrared spectroscopy, X-ray diffraction patterns and X-ray photoelectron spectra results proved the formation of CS-MgO and CS-NiO nanocomposites. Also, the particle sizes were observed to be 18.3 and 25.5 nm for CS-NiO and CS-MgO, respectively. All the samples exhibited antibacterial activities against the Escherichia coli and Staphylococcus aureus strains; however, more effective against S. aureus compared to E. coli. Noticeably, 5 mu g/mL CS-NiO comparatively exhibited highest bactericidal capability where E. coli and S. aureus viabilities were reduced to 25-47% after 12 h incubation. After treatment with 15 mu g/mL of CS-NiO, similar to 98% of S. aureus and 92.3% of E. coli cells were inhibited.
Keywords: Antibacterial properties; chitosan metal oxide; polymeric nanocomposites; NiO; MgO; Escherichia coli